Pedicled-Perforator (Propeller) Flaps in Lower Extremity Defects: A Systematic Review - Gir, Phanette; Cheng, Angela; Oni, Georgette; Mojallal, Ali; Saint-Cyr, Michel (Journal of Reconstructive Microsurgery, 2012)
Pedicled-perforator (propeller) flaps for lower extremity reconstruction have gained popularity due to minimal donor site morbidity, relatively simple surgical technique, and replacement of tissue using “like-by-like” principles. We reviewed and analyzed the clinical use of these flaps in regards to patient age and gender, etiology and location of the defect, size and type of flap, arc of rotation, and complications to determine the reliability of this technique. A systematic review of the PubMed database using search terms to include perforator, pedicled, and propeller flaps in the lower extremity. Data from 15 case series provided 186 cases of pedicled-perforator (propeller) flaps for analysis using Chi-square tests. The Peroneal Artery Perforator (PAP) flaps and Posterior Tibial Artery Perforator (PTAP) flaps were the most frequently used flaps. The overall complication rate was 25.8% and the failure rate was 1.1%. No significant differences were found in complication rate related to age, gender, etiology or location of the defect, type or size of the flap. The most common complications were partial flap loss and venous congestion (11.3 and 8.1%). Pedicled-perforator flaps appear to be a reliable and safe procedure for the coverage soft tissue defects of the lower extremity based on favorable results reported in the literature.
Keywords: propeller flap; perforator flap; lower extremity